Graphic Interlude: Digital Subjectivities - Claire Larsonneur (Angles)
This graphic interlude features a selection of pictures from Figures urbaines, a photographic series by Claire Larsonneur, which was displayed at the Usine Utopik and the château of Cerisy la Salle during the Posthuman seminar in June 2016. Each picture echoes an excerpt from science-fiction. All photographs were taken in public spaces and are unedited: those urban figures were graffiti, shop displays, reflections and may no longer exist.